Management of Involuntary Self-Mutilation in a Child with Lesch-Nyhan Syndrome - Lertsirivorakul, Jinda; Wichajarn, Khunton; Tiamkao, Somsak; Chawyotha, Panawat (Khon Kaen University Dental Journal, 2020)
Lesch–Nyhan syndrome (LNS) is a rare X-linked recessive disorder of purine metabolism caused by deficiency of the enzyme hypoxanthine guanine phosphoribosyltransferase (HPRT). It is characterized by hyperuricemia, neurologic dysfunction, and self-mutilation. Medical and dental management in a 10-year-old boy diagnosed with LNS are described. Involuntary self-mutilation could be controlled using a soft mouth guard and repeated injections of botulinum toxin A (BTX-A) into the bilateral masseter and temporalis muscles. The findings suggest that patients with LNS require treatment from a multidisciplinary team. In addition, a soft mouth guard, repeated BTX-A injections, and pharmacological therapy could be a promising management of involuntary self-mutilation in LNS patients.